Acute procedural outcomes of his bundle pacing with or without electrophysiology mapping system: a multicenter study. (4th February 2022) - Loo, G; De Leon, J; Seow, S C; Boey, E; Soh, R; Tan, E; Gan, H H; Lee, J Y; Teo, J T L; Yeo, C; Kojodjojo, P; Tan, V H
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction His bundle pacing (HBP) is associated with improved clinical outcomes compared to right ventricular apical pacing. However, it can be technically challenging and may result in prolonged fluoroscopy and procedural time. Purpose We sought to compare the feasibility of performing HBP with or without electrophysiology mapping (EP) system, focusing on evaluating acute procedural success, complication rates and short-term outcomes. Methods HBP patients at 3 hospitals were recruited between August 2018 to December 2020. HBP was performed with EP mapping system in 1 center, and without EP mapping in the other 2 centers. Acute procedural success was defined as either selective or non-selective His bundle capture with a threshold of less than or equal to 1.5V at 1ms at the end of procedure implantation. Results A total of 233 patients were recruited, of which HBP was performed with EP mapping in 77 patients (33.0%) and without EP mapping in 156 patients (67.0%). Both groups were similar in age (73.2 ± 11.0 years vs 75.3 ± 9.5 years, p = 0.125) and male sex (58.4% vs 48.1%, p = 0.136). There were more patients with ischemic heart disease (45.5% vs 22.4%, p < 0.01) and reduced left ventricular ejection fraction ≤ 40% (28.6% vs 10.9%, p < 0.01) in the group with EP mapping. The indications for HBP was for high-grade atrioventricular block (55.8%), sick sinus syndrome (35.6%) and cardiac resynchronization therapy (CRT) (8.6%). There were more patients who required CRT in the center with EP mapping (18.2% vs 3.8%, p < 0.01). HBP was successful in 39 patients (50.6%) with EP mapping and 93 patients (59.6%) without EP mapping (p= 0.382). The median R wave at implant was similar in both groups [4.0 (2.9 – 6.2) mV vs 4.3 (4.3 – 7.0) mV, p = 0.808]. Impedance at implant (607 ± 195 ohms vs 547 ± 166 ohms, p < 0.01) and selective His bundle bipolar threshold at implant [1.25 (0.75-1.75) V vs 0.7 (0.5 – 1.25) V, p = 0.01] was higher in patients with EP mapping while non-selective His bundle bipolar threshold at implant [1.75 (1.0 – 3.0) V vs 1.5 (0.9 – 2.2) V, p = 0.133] and paced QRS duration (116.4 ± 25.4 ms vs 114.4 ± 24.2 ms, p =0.655) were similar. There were no differences in procedural or fluoroscopy time between groups (111 ± 36.9 min vs 107 ± 40.7 min, p = 0.479; and 10.3 ± 8.9 min vs 12.1± 14.0 min, p = 0.328 respectively). There was a similar rate of acute procedural complications (5.2% vs 1.3%, p = 0.076) and patients requiring wound or lead revision (6.8% vs 1.9%, p = 0.115) after a median follow up duration of 205 days (67-397). The prevalence of new onset paroxysmal atrial fibrillation  (11.7% vs 4.2%, p = 0.037) and all cause mortality (12.3% vs 3.2%, p = 0.029) was increased in patients who underwent HBP with EP mapping. Conclusion: HBP in centers with or without EP mapping showed similar acute procedure success and complication rates. The use of EP mapping system was not shown to affect procedural or fluoroscopy duration.